2013
DOI: 10.4103/0972-124x.107474
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of subgingival plaque microflora in pregnant and non-pregnant women: A clinical and microbiologic study

Abstract: Context:Gingival changes in pregnancy have been attributed to changes in the subgingival biofilm related to hormonal variations.Aims:To evaluate the subgingival plaque microflora in pregnant and nonpregnant women to determine if pregnancy induces any alterations in the subgingival plaque and to associate these changes with changes in periodontal status.Settings and Design:Thirty pregnant and 10 nonpregnant women within the age group of 20-35 years having a probing pocket depth (PPD) of 3-4 mm were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 10 publications
3
20
1
1
Order By: Relevance
“…23 Although in the healthy state, there is a balance between microbiota virulence factors and host defense factors, if this equilibrium is disrupted by microbial or host factors, including hormonal changes during pregnancy, these specific pathogens can increase in number and lead to the development of periodontal disease (gingivitis and periodontitis). Although these aspects were not evaluated in this study, this theory is accepted by other authors 13,15 who have suggested that P. gingivalis, P. nigrescens, C. rectus, and A. actinomycetemcomitans can be implicated as risk factors for adverse pregnancy outcomes, including prematurity and low birth weight.…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…23 Although in the healthy state, there is a balance between microbiota virulence factors and host defense factors, if this equilibrium is disrupted by microbial or host factors, including hormonal changes during pregnancy, these specific pathogens can increase in number and lead to the development of periodontal disease (gingivitis and periodontitis). Although these aspects were not evaluated in this study, this theory is accepted by other authors 13,15 who have suggested that P. gingivalis, P. nigrescens, C. rectus, and A. actinomycetemcomitans can be implicated as risk factors for adverse pregnancy outcomes, including prematurity and low birth weight.…”
mentioning
confidence: 73%
“…Most studies on periodontal microbiota have used cultures, 12,15,19 conventional PCR, 22 real-time PCR, 14 checkerboard DNA-DNA hybridization, 9,16,23 and, most recently, DNA sequencing technologies. 24 However, because these approaches are based on various parameters and have differing sensitivities, it is very difficult to compare the results to clearly elucidate microbial community structure.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
See 2 more Smart Citations
“…4B). This is in agreement with periodontal pathogens presence found in the analysis of subgingival microbial composition of pregnant women who experienced increased gingival inflammation (Borgo et al, 2014;Emmatty et al, 2013). As a result of exacerbated gingival inflammation, some women developed permanent periodontal tissue damage and alveolar bone loss (Christensen et al, 1998;Lieff et al, 2004;Machuca et al, 1999;Moss et al, 2005;Taani et al, 2003).…”
Section: Reduced Oral Bacteria Clearancesupporting
confidence: 73%